Gaslight - (:unkn) unknown (My University, 2016)
Gaslight is an exploration of the psychological phenomena of “gaslighting” in abusive relationships. Sensations of disorientation, insecurity, and the overwhelming feeling of being trapped are metaphorically imbued in the soft sculptural objects installed within the confines of the gallery space. In conjunction with the crocheted soft sculptures, the use of fabricated shadows also manipulates the viewer into questioning the physical truth of the art objects. Reality is further blurred as the objects extend their capacity of occupying space, drawing the viewer in to inspect whether or not the shadows that they are seeing are true projections or ghosts from previous presences of light. Through dim lighting, drawn shadows, and webbed forms, the small-scale installations in Gaslight take on the role of the manipulator—manipulating the viewer to confront emotions regarding entrapment and self-doubt.
Keywords: Affect Theory; Art; Crochet; Drawing; Installation Art; Sculpture